Peringkas Otomatis Teks Berbahasa Arab Menggunakan Algoritma TextRank - Muhammad Fikri Hidayattullah; Ardhiyan Azizi (Jurnal Ilmiah Informatika, 2021)
Increasingly, the amount of data in the form of text documents scattered on the internet is getting bigger. It took a very long time to get the information from each of these documents. For this reason, several researchers developed the Automatic Text Summarizer to summarize text automatically, so that the time needed to get important information from the entire document can be faster. Research that focuses on automatic summarization of Arabic texts is very rare. In fact, there are more than 300 million Arabic speakers in the world and Arabic is the official language at the United Nations. Therefore, this study develops a model that can perform text summarization automatically using the TextRank algorithm. The test results using Q&A Evaluation show very good results with details of the suitability of the summary results with the original text by 90%, the suitability of the summary results with Arabic grammar is 91.43%, the suitability of the summary results is 90%, the ease of understanding the summary results is 90%. and the useful aspects of the model developed were 91.43%.